Leporine model refinement for investigation of an ophthalmic dynamic light scattering instrument - Dubin, S.; Ansari, R.R.; Victor, M.; Koch, S.; Steinberg, S.; VanWinkel, T.; Della Vecchia, M. (Northeast Bioengineering Conference, 1998, 1998)
Evaluation of lens opacity is indispensable in human clinical monitoring as well as research. The rapid evolution of ophthalmic instrumentation impels the development of models which are anatomically and physiologically realistic; and, at the same time, minimally intrusive to the nonhuman animal subjects. Use of an appropriate dosage regimen and other technical refinements for administration of naphthalene in the rabbit can reliably cause lens opacity and chorioretinal changes with much diminished danger or distress.